Unifying science through computation: Reflections on computability and physics - John Tucker (2012)
Edwin Beggs, José Félix Costa, and John V. Tucker. Unifying sciencethrough computation: Reflections on computability and physics. OlgaPombo, Juan Manuel Torres, John Symons, and S. Rahman (editors):Special Sciences and the Unity of Science, Book series: Logic,Epistemology, and the Unity of Science, Vol. 24: 53--80, Springer,2012.